IoT Empowered Harvest: Advancing NFT Hydroponics with Smart Agricultural Automation - Ghate, Trupti; Malpe, Kalpana (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
For every nation, farmers play the most essential role and that is to feed the population. In the urban areas there is lack of open green space for farming and even if the land is available it is infertile for plants to grow on them. Problems faced in urban areas farms are due to the toxic elements let in the soil. The sources of toxic metals and effluents in urban soils are mainly from emissions from industries, automobiles, industrial as well as domestic sewage. In urban areas, people are busy in their work which leads them to buy pesticide and chemically treated food which in injurious to health and they are unable to grow organic vegetable at home due to deficit of space, time and un-fertile soil.Hydroponics is the method of cultivating plants without soil. Water with oxygen and required minerals acts as the cultivation medthod. Smart Hydroponic Farming using the NFT Method helps the farmer to stay connected to their farm anytime and anywhere. This hydroponic system requires special attention to several parameters such as the water temperature, water level, acidity (pH), and the concentration of the nutrient (EC/PPM). We first monitor and collect information from NFT Hydroponic farmer and then systematically evaluate and analyze them. Unfortunately, it is still controlled by using the conventional way (human), for example in controlling the concentrations of nutrient has to be done at least once a day, so much time is wasted. In addressing these issues, we need a system that can be applied and used easily.We built a hydroponic monitoring and automation system that can monitored using sensors connected to the Arduino Uno microcontrollerm, Wi-Fi module ESP8266 and Raspberry Pi 2 Model B microcomputers as the webserver with the concept Internet of Things, in which each block hydroponic farming can communicate with the webserver (broker). Web used as the interface of the system that allows user to monitor and control the NFT hydroponic farming. The NFT hydroponic web interface management systems using a responsive web framework, such as Bootstrap for the front-end, JQuery and JavaScript libraries. The result shows that this system helps farmers to increase the effectivity and efficiency on monitoring and controlling NFT Hydroponic Farm.
Keywords: Hydroponic Farming; Nutrient Film Technique; Internet of Things; Urban Farming; Arduino Uno Microcontrollerm; Wi-Fi module ESP8266; Raspberry Pi 2 Model B